Shipping Cattle, Not Tropical Soda Apple Seed - Jeffrey Mullahey; Patrick Hogue; Jason Ferrell; Brent Sellers (EDIS)
Revised! SS-AGR-78, a 2-page fact sheet by Jeff Mullahey, Pat Hogue, Jason Ferrell, and Brent Sellers, encourages cattlemen to take precautions to avoid transmitting TSA when shipping cattle. This version includes updated herbicide recommendations and a list of resources for further information. Published by the UF Department of Agronomy, August 2006.